An investigation into image-based indoor localization using deep learning - Li, Qing (2020)
Localization is one of the fundamental technologies for many applications such as location-based service ( LBS ), robotics, virtual reality ( VR ), autonomous driving, and pedestrians navigation. Traditional methods based on wireless signals and inertial measurement unit (IMU) have inherent disadvantages which limit their applications. Although image-based localization methods seem to be promising supplements to previous methods, their applications in the indoor scenario have many challenges. Compared to the outdoor environments, indoors are more dynamic which adds difficulty to map construction. Also, indoor scenes tend to be more similar to each other which makes it difficult to distinguish different places with a similar appearance. Besides, how to utilize widely available 3D indoor structures to enhance the localization performance remains to be well explored.